Naphthalenediimides with Cyclic Oligochalcogenides in Their Core. Issue 62 (1st October 2020) - Shybeka, Inga; Aster, Alexander; Cheng, Yangyang; Sakai, Naomi; Frontera, Antonio; Vauthey, Eric; Matile, Stefan
Abstract: Naphthalenediimides (NDIs) are privileged scaffolds par excellence, of use in functional systems from catalysts to ion channels, photosystems, sensors, ordered matter in all forms, tubes, knots, stacks, sheets, vesicles, and colored over the full visible range. Despite this extensively explored chemical space, there is still room to discover core‐substituted NDIs with fundamentally new properties: NDIs with cyclic trisulfides (i.e., trisulfanes) in their core absorb at 668 nm, emit at 801 nm, and contract into disulfides (i.e., dithietes) upon irradiation at <475 nm. Intramolecular 1, 5‐chalcogen bonds account for record redshifts with trisulfides, ring‐tension mediated chalcogen‐bond‐mediated cleavage for blueshifts to 492 nm upon ring contraction. Cyclic oligochalcogenides (COCs) in the NDI core open faster than strained dithiolanes as in asparagusic acid and are much better retained on thiol exchange affinity columns. This makes COC‐NDIs attractive not only within the existing multifunctionality, particularly artificial photosystems, but also for thiol‐mediated cellular uptake. Abstract : Privileged scaffolds par excellence, colored over the full visible range, multifunctionality driven to the extreme, yet there is still room for simple core‐substituted NDIs with completely new properties. Trisulfanes crack persistent redshift records, contract into 176 nm blueshifted dithietes upon irradiation at <475 nm, thanks to chalcogen bonds and ring tension, open fast and release slow, thus inviting for thiol‐mediated cellular uptake.